Ceramic material for hot bending mold and preparation method thereof
By using boron carbide skeleton materials and nitriding treatment technology, the problem of high-purity and high-density graphite molds is solved, and a more durable ceramic mold is achieved, which improves the preparation efficiency and product quality of the curved glass on the back plate of smartphones. .
Patent Information
- Application Number
- CN202410712862.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-06-04
AI Technical Summary
Existing high-purity high-density graphite hot bending molds are prone to oxidation at high temperatures, resulting in short service life and high cost, and it is difficult to meet the efficient preparation needs of curved glass on the back plate of smartphones.
Boron carbide skeleton material is made of 20μm boron carbide micropowder, 1μm boron carbide micropowder, maleic anhydride copolymer, polyethylene glycol, glycerol, polyvinyl alcohol and other raw materials, and is subjected to ball milling dispersion, spray granulation, dry pressure Cold isostatic molding and sintered at high temperature to form a porous structure. Then, boron trioxide and nitriding are filled in a vacuum furnace to form layered boron nitride deposition to enhance antioxidant and thermal shock resistance.
It significantly improves the high temperature resistance and oxidation resistance of the mold, extends the service life, reduces production costs, and improves the preparation efficiency and product yield of 3D glass.
Smart Images

Figure CN118598666B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new material manufacturing, and in particular to a ceramic material for a hot bending mold and a preparation method thereof. Background Art
[0002] With the advent of the 5G boom, smartphones have become more and more demanding in terms of signal transmission. In addition, the accelerated penetration of technologies such as wireless charging in the mobile phone market has caused the metal casings that have served the smartphone industry for many years to gradually withdraw from the market. Glass, ceramics, sapphire and other hard and brittle materials have become popular materials, especially glass back panels, which have the advantages of good wave transmission, good feel, simple processing and low cost, and have become the preferred material for mainstream mobile phone back panels. At the same time, curved screens are generally favored and sought after by smart electronic products, which has led to changes and developments in the supporting supply industry. Some equipment manufacturers have invested in the research and development of curved glass preparation very early, and all use the same curved glass forming method, that is, placing flat glass (called "2D glass") in the hot working mold cavity, placing the hot working mold in the hot bending equipment, and raising it to a high temperature state. The hot bending equipment is usually continuously filled with inert gas to prevent the product and the various parts of the mold from being oxidized; when the glass reaches a softened state, the mold is pressed and formed into the required curved glass (called "3D glass"). In the hot bending equipment, a very important consumable is the molding mold that is in direct contact with the glass.
[0003] The commonly used 3D hot bending mold material is high-purity and high-density graphite. Because of its soft texture, it is easy to process and polish, and it is easy to demold due to its non-wetting properties with glass. The temperature during the hot bending process of glass is around 750-800℃. Graphite is easily oxidized at this temperature, resulting in oxidation corrosion pits on the graphite surface, which often makes the graphite mold have a short service life and a high replacement frequency. In addition, the graphite material used is often imported, resulting in high production costs.
[0004] Therefore, mold material becomes an important factor restricting the efficiency, cost, and yield rate of 3D glass hot bending. It is necessary to develop a new mold material to increase the service life of hot bending molds and reduce production costs. Summary of the invention
[0005] Purpose of the invention: In view of the deficiencies in the prior art, the present application provides a ceramic material for hot bending molds and a preparation method thereof, which can be used to replace graphite materials.
[0006] Technical solution: The present invention provides a ceramic material for preparing a hot bending mold. The ceramic material is made of 20μm boron carbide powder, 1μm boron carbide powder, maleic anhydride copolymer, polyethylene glycol, propylene glycol, and polyvinyl alcohol as raw materials to form a boron carbide skeleton. The porosity of the boron carbide skeleton is 8-12%, and layered boron nitride is deposited in the pores of the boron carbide skeleton.
[0007] The present invention also provides a method for preparing the ceramic material: accurately weigh 20 μm boron carbide powder, 1 μm boron carbide powder, maleic anhydride copolymer, polyethylene glycol, glycerol, polyvinyl alcohol, and deionized water according to weight, add them into a ball mill after mixing, and disperse them by ball milling. During the ball milling dispersion process, the raw material particles are refined and evenly distributed by mechanical force, the stability of the slurry is improved, and the foundation for subsequent granulation and molding is laid. The grinding time is 5-6 hours, and each component is divided into a uniform slurry, and then the uniformly ground slurry is sprayed and granulated to make the slurry into a spherical powder. The fluidity and filling properties of the powder are improved, which is convenient for subsequent molding operations and is also conducive to improving the uniformity and density of the green body.
[0008] The molding is carried out by dry pressing + cold isostatic pressing. The initial molding is carried out by dry pressing, and then the density and uniformity of the green body are improved by cold isostatic pressing technology. The formed ceramic green body is placed in a vacuum sintering furnace for high-temperature sintering. The sintering temperature is 2300±10℃ and the temperature is kept for 2-3h. High-temperature sintering promotes interfacial reaction and volume diffusion between particles to form a continuous crystalline phase structure, thereby improving the physical and mechanical properties of the ceramic. The 20-micron large particles accumulate to form a porous skeleton structure. Under the action of high temperature, the 1-micron fine powder grows at the contact neck of the large particles through evaporation condensation mass transfer, strengthens the skeleton structure of the large particles, and enables the ceramic to obtain higher strength. At the same time, the porous structure gives the ceramic excellent thermal shock resistance. The sintering density of the present invention after high-temperature sintering is about 2.2-2.35g / cm 3 At this time, the porosity of the sintered ceramic is about 10%.
[0009] The sintered boron carbide skeleton is placed in a graphite crucible and covered with boron trioxide powder. The crucible is then placed in a vacuum furnace, evacuated, and heated to 800-900°C (preferably 859°C) for 2-3 hours to allow the boron trioxide to fully fill the boron carbide skeleton.
[0010] After cooling, the boron carbide skeleton impregnated with boron trioxide is taken out, and the boron trioxide on the surface of the boron carbide skeleton is removed by a sandblaster. The boron carbide skeleton is placed in a tubular nitriding furnace for nitriding treatment. Ammonia is introduced first, and then three stages of heating are performed for 6-12 hours, and the final temperature is 1200°C. During the heating process, boron trioxide can decompose and release free boron atoms. The generated boron atoms can move freely in the pores, which is conducive to the uniform nitriding process. The nitriding reaction not only forms a layer of boron nitride coating on the surface of the boron carbide, but also forms boron nitride deposition inside the pores because ammonia can penetrate into the porous structure.
[0011] Then, the nitrided composite material is subjected to surface grinding to remove the surface nitrided layer. Finally, the ceramic blank is processed into the desired shape by a CNC milling machine, and the mold surface is polished with a polishing paste.
[0012] Specifically, the raw material ratio is: 80-95 parts of 20 μm boron carbide powder, 5-20 parts of 1 μm boron carbide powder, 1 part of maleic anhydride copolymer SMA2000, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol, and 80-100 parts of deionized water.
[0013] Specifically, the ball mill: the grinding balls are boron carbide balls with a diameter of 10 mm, and the ball-to-material ratio is 3:1.
[0014] Specifically, the green density of the molding after isostatic pressing is controlled at 1.75±0.05g / cm 3 .
[0015] Specifically, the amount of the boron trioxide used is 5 times the mass of the boron carbide skeleton.
[0016] Specifically, the three-stage heating is as follows: the first stage: temperature 350°C, heat preservation for 2h, ammonia flow rate of 15ml / min; the second stage: temperature 800°C, heat preservation for 1h, ammonia flow rate of 35ml / min; the third stage: temperature 1200°C, heat preservation for 3h, ammonia flow rate of 5ml / min. The heating rate between each stage is about 5°C / min. For the present invention, in order to form layered boron nitride deposition, the heating method is more critical. The temperature of the first stage is 350°C, which is mainly to activate the decomposition reaction of ammonia. Ammonia is gradually decomposed into active nitrogen and hydrogen under heating conditions. At the same time, at this temperature, the water inside the material gradually evaporates, creating favorable conditions for subsequent chemical reactions. The slow heating of the low temperature stage helps to avoid thermal stress inside the material and protect the skeleton structure from damage. The temperature of the second stage is 800°C, the activity of the decomposed nitrogen atoms is enhanced, and chemical reactions begin to occur with the surface of boron carbide to form a boron nitride coating. The increase in ammonia flow promotes the effective transfer and reaction rate of nitrogen. At the same time, higher temperatures accelerate the kinetic process of chemical reactions, making the nitridation reaction more sufficient. The temperature of the third stage is 1200°C. In addition to the continued nitriding reaction on the surface, a deeper nitriding process is achieved. The reduction of ammonia flow is to control the quality of the nitriding layer and avoid coating defects caused by too fast a reaction rate. Under high temperature, the boron trioxide inside the pores can also be completely decomposed, and the released boron atoms react with nitrogen to form more boron nitride deposited in the pores, enhancing the structural integrity and performance of the composite material. This stage is also to ensure the thorough completion of the nitriding process and form a uniform and dense layered boron nitride deposition. In addition, the three-stage heating and control of ammonia flow of the present invention can effectively avoid defects such as bubbles and cracks caused by rapid heating and overreaction, thereby ensuring the surface finish and internal structural integrity of the final product.
[0017] For the present invention, if the amount of 20μm boron carbide powder is large, that is, when the ratio of 20μm boron carbide powder to 1μm boron carbide powder is greater than 9:1 (for example, 90 parts of 20μm boron carbide powder and 10 parts of 1μm boron carbide powder), although the thermal shock resistance and oxidation resistance are better, the surface roughness is not ideal. In view of this situation, further improvements can be made, and secondary nitriding treatment can be performed after polishing. The specific operation is: a certain amount of boron trioxide powder is sprinkled on the surface of the working surface, and then placed in a vacuum furnace, vacuumized, and heated to 850℃, kept warm for 2h, and after the boron trioxide melts, a layer of boron trioxide glaze layer will be formed on the surface of the working surface. Then it is placed in a nitriding furnace for nitriding treatment, and the generated boron nitride will fill the pores to ensure that the working surface is smooth and flat without pores. The conditions for the secondary nitriding treatment are: temperature 1200℃, insulation 5h, and ammonia flow rate of 5ml / min.
[0018] Beneficial effects: The present invention uses boron carbide-based composite ceramic materials to replace traditional high-purity and high-density graphite as the material of the 3D hot bending mold, which significantly improves the high temperature resistance and oxidation resistance of the mold. Boron carbide itself has an extremely high melting point and good thermal stability, and the deposition of boron nitride further enhances the corrosion resistance and wear resistance of the surface, effectively avoiding the problem of easy oxidation corrosion of graphite molds at high temperatures, thereby greatly extending the service life of the mold and reducing the cost of frequent mold replacement.
[0019] The porous structure of the boron carbide skeleton combined with the internal boron nitride deposition not only maintains the high strength of the material, but also gives it excellent thermal shock resistance, allowing it to withstand rapid temperature changes during hot bending without damage. At the same time, this design is conducive to uniform heat transfer, reduces thermal stress concentration, and improves processing accuracy and product yield.
[0020] The mold prepared by the hot working mold material provided by the present invention can ensure high-precision size control and surface finish of the mold, and the obtained mold has the advantages of high surface hardness, touch or slight collision will not damage the mirror surface of the mold molding surface, and there is no slight detachment on the mold surface. As a result, the surface of the 3D glass finally prepared is smooth, without scratches and bumps. In addition, compared with traditional molds, the mold material of the present invention has better thermal conductivity, so that the mold of the present invention has advantages such as fast heating and cooling rates when used in the manufacturing process of curved glass, thereby significantly improving the production efficiency per unit time.
[0021] The ceramic material for hot bending molds provided by the present invention has high temperature resistance and stable performance in harsh working environments, long service life, reduces resource waste and environmental pollution caused by material failure, and is in line with the modern manufacturing industry's pursuit of sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Optical microstructure photograph of coarse powder boron carbide after spray granulation.
[0023] Figure 2 : SEM image of boron carbide after boron nitride deposition (10 μm).
[0024] Figure 3 : SEM image of boron carbide after boron nitride deposition (1 μm).
[0025] Figure 4 : SEM image of boron nitride in the pores.
[0026] Figure 5 : Optical microstructure photos of nitride ceramic surface after grinding.
[0027] Figure 6 : A hot bending mold made from the material obtained in Example 1. DETAILED DESCRIPTION
[0028] The technical solution of the present application is described in detail below through examples, but the protection scope of the present application is not limited to the examples. The parts described in the present embodiment are all parts by mass.
[0029] Example 1
[0030] The following components are accurately weighed according to weight: 80 parts of 20 micron boron carbide, 20 parts of 1 micron boron carbide, 1 part of maleic anhydride copolymer SMA2000, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol, and 80-100 parts of deionized water. After mixing, add them into a ball mill for ball milling dispersion. The grinding balls are boron carbide balls with a diameter of 10 mm, the ball-to-material ratio is 3:1, and the grinding time is 6 hours. Each component is granulated into a uniform slurry. The uniformly ground slurry is spray granulated to make the slurry into a spherical powder, such as Figure 1 shown.
[0031] The molding process is carried out by dry pressing + cold isostatic pressing. The green density after isostatic pressing is 1.77g / cm 3 The formed ceramic green body was sintered in a vacuum sintering furnace at a high temperature of 2290°C for 2 hours to obtain a porous boron carbide skeleton. The density of the sintered ceramic skeleton was 2.34 g / cm 3 .
[0032] The porous boron carbide skeleton is placed in a graphite crucible and buried with boron trioxide powder 5 times the mass of the boron carbide skeleton. The crucible is then placed in a vacuum furnace, evacuated, and heated to 859°C for 2 hours to allow the boron trioxide to fully fill the boron carbide skeleton.
[0033] After cooling, take out the boron carbide skeleton impregnated with boron trioxide, and use a sandblaster to remove the boron trioxide on the surface of the boron carbide skeleton. Place the boron carbide skeleton in a tubular nitriding furnace for nitriding treatment. First, introduce ammonia, and then heat it in three stages: the first stage: temperature 350°C, keep warm for 2 hours, ammonia flow rate of 15ml / min; the second stage: temperature 800°C, keep warm for 1 hour, ammonia flow rate of 35ml / min; the third stage: temperature 1200°C, keep warm for 3 hours, ammonia flow rate of 5ml / min. The heating rate between each stage is about 5°C / min. The ceramic material described in the present invention is obtained, such as Figure 2 , Figure 3 As shown in Figure 1, boron nitride is deposited in the pores of the boron carbide skeleton. The morphology of boron nitride in the pores is as follows: Figure 4 shown.
[0034] The ceramics after nitriding treatment are ground to make the surface smooth and flat without pores. Figure 5 As shown. Finally, the ceramic blank is processed into the desired shape by a CNC milling machine, and its surface is polished with polishing paste. The surface roughness Ra after polishing is 0.44nm.
[0035] Example 2
[0036] The basic steps of this embodiment are roughly the same as those of Embodiment 1, except that:
[0037] The raw material components are: 85 parts of 20 micron boron carbide, 15 parts of 1 micron boron carbide, 1 part of maleic anhydride copolymer SMA2000, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol, and 80-100 parts of deionized water.
[0038] The green density of this embodiment after molding is 1.75g / cm 3 The density of the ceramic skeleton after sintering in this embodiment is 2.28g / cm 3 The surface roughness Ra of the product of this embodiment after polishing is 0.59 nm.
[0039] Example 3
[0040] The basic steps of this embodiment are roughly the same as those of Embodiment 1, except that:
[0041] The raw material components are: 90 parts of 20 micron boron carbide, 10 parts of 1 micron boron carbide, 1 part of maleic anhydride copolymer SMA2000, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol, and 80-100 parts of deionized water.
[0042] The green density of this embodiment after molding is 1.69g / cm 3 The ceramic skeleton density after sintering in this embodiment is 2.21g / cm 3The surface roughness Ra of the product in this embodiment after polishing is 0.89 nm.
[0043] From Examples 1 to 3, it can be seen that the surface roughness of Example 1 is the most ideal, and the surface of Example 3 is the roughest. This is because Example 3 has more coarse boron carbide powder and larger internal pores, and the flatness of the product after polishing is not as good as that of Example 1.
[0044] The performance parameters of the products obtained in Examples 1 to 3 are shown in the following table:
[0045]
[0046] The thermal shock resistance test was conducted on the products obtained in Examples 1 to 3. The specific process is: the sample is heated to 1000°C in a muffle furnace, taken out and cooled in air for 5 minutes, and then placed in water at 25°C, and the cycle is repeated several times to observe the cracking of the sample. The test results are shown in the table below.
[0047]
[0048] The products obtained in Examples 1 to 3 were tested for their antioxidant properties. The specific process is: after weighing the sample, place it in a tubular reactor, continuously introduce oxygen at a temperature of 800°C and a pressure of 2MPa, take out the sample after different time periods and weigh it again, and calculate the weight loss rate. The test results are shown in the following table:
[0049] Weight loss rate (1h) Weight loss rate (6h) Weight loss rate (12h) Example 1 0 <0.1% <0.3% Example 2 0 <0.1% <0.2% Example 3 0 <0.1% <0.1%
[0050] It can be seen that the mechanical properties of the products obtained in Examples 1 to 3 can all be used for 3D glass hot bending mold materials, and at the same time, they all have good hardness and thermal conductivity. In comparison, the surface smoothness of Example 1 is the best. Although the surface smoothness of the product obtained in Example 3 is not as good as that of Examples 1 and 2, it has the best thermal shock resistance and oxidation resistance, that is, the longest service life.
[0051] Example 4
[0052] This example is a further improvement of Example 3, and its basic steps are substantially the same as those of Example 3, and its raw material components are the same as those of Example 3. The difference is that:
[0053] After polishing, it is subjected to secondary nitriding treatment. The specific operation is: a certain amount of boron trioxide powder is sprinkled on the surface of the working surface, and then the vacuum furnace is evacuated and heated to 850℃, and the temperature is kept for 2 hours. After the boron trioxide melts, a layer of boron trioxide glaze will be formed on the surface of the working surface. Then it is placed in a nitriding furnace for secondary nitriding treatment. The conditions of the secondary nitriding treatment are: temperature 1200℃, heat preservation 5h, ammonia flow rate 5ml / min.
[0054] The final surface roughness Ra of the product in this embodiment is 0.45 nm. For the present invention, after further improvement, the surface roughness of the product can reach the effect of embodiment 1, and its service life can reach the effect of embodiment 3.
[0055] Application Examples
[0056] The material obtained in Example 1 of the present invention is prepared into a mold. Figure 6 As shown, the mold is used to prepare 3D curved glass with a pass rate of >99%. The curved glass obtained by molding has no scratches or bumps on the surface and is easy to process.
[0057] Comparative Example 1
[0058] The basic steps of this comparative example are roughly the same as those of Example 1, except that:
[0059] The raw material components are: 100 parts of 20 micron boron carbide, 1 part of maleic anhydride copolymer SMA2000, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol, and 80-100 parts of deionized water.
[0060] The obtained silicon carbide ceramic cannot form an ideal pore structure and is not suitable for the subsequent immersion nitriding step.
[0061] Comparative Example 2
[0062] The basic steps of this comparative example are substantially the same as those of Example 1, except that after sintering into a ceramic skeleton, the silicon carbide ceramic is directly polished without undergoing an immersion nitriding operation.
[0063] The obtained product has low density and strength, and there are a large number of holes on the surface of the silicon carbide blank, which is not suitable as a mold material.
[0064] Comparative Example 3
[0065] Boron nitride deposition is not achieved by using the method described in the present invention, but the boron carbide particles and the boron nitride particles are mechanically mixed and fired into shape.
[0066] Although the mechanical properties of the obtained product are acceptable, powder will fall off. This is mainly because the two particles that have not been chemically bonded are mainly in physical contact, and the interface bonding force is weak. When subjected to extreme working conditions such as high stress or high temperature, the particles are prone to fall off or separation, affecting the stability and durability of the material.
Claims
1. A ceramic material for a hot bending mold, characterized in that: The ceramic material comprises a boron carbide skeleton and layered boron nitride. The boron carbide skeleton is made of 20 μm boron carbide powder, 1 μm boron carbide powder, maleic anhydride copolymer, polyethylene glycol, glycerol, polyvinyl alcohol and deionized water as raw materials. The porosity of the boron carbide skeleton is 8-12%, and the layered boron nitride is deposited in the pores of the boron carbide skeleton.
2. The method for preparing a ceramic material for a hot bending mold according to claim 1, characterized in that: The steps include: The boron carbide powder of 20 μm, the boron carbide powder of 1 μm, the maleic anhydride copolymer, the polyethylene glycol, the glycerol, the polyvinyl alcohol and the deionized water are accurately weighed according to the weight parts, and after mixing, they are added into a ball mill for ball milling dispersion. The ball milling time is 5-6 hours. The components are ball milled and dispersed to obtain a uniform slurry. Then, the uniformly ground slurry is sprayed and granulated to make the slurry into a spherical powder. The molding is carried out by dry pressing + cold isostatic pressing. The formed ceramic green body is placed in a vacuum sintering furnace for high-temperature sintering. The sintering temperature is 2300±10℃ and the temperature is kept for 2-3h. The sintered boron carbide skeleton is placed in a graphite crucible and buried with boron trioxide powder; the crucible is then placed in a vacuum furnace, evacuated, and heated to 800-900°C for 2-3 hours to allow boron trioxide to fully fill the boron carbide skeleton; after cooling, it is taken out, the boron trioxide on the surface of the boron carbide skeleton is removed, and then it is placed in a tubular nitriding furnace for nitriding treatment, and ammonia is introduced for three-stage heating for 6-12 hours; The nitrided ceramic material is subjected to surface grinding to remove the surface nitrided layer; finally, the ceramic blank is processed into the desired shape by a CNC milling machine, and the mold surface is polished with a polishing paste.
3. The method for preparing a ceramic material according to claim 2, characterized in that: The raw material ratio is: 80-95 parts of 20μm boron carbide powder, 5-20 parts of 1μm boron carbide powder, 1 part of maleic anhydride copolymer, 2 parts of polyethylene glycol, 1 part of glycerol, 3 parts of polyvinyl alcohol and 80-100 parts of deionized water.
4. The method for preparing a ceramic material according to claim 2, characterized in that: The ball mill described herein is a boron carbide ball with a diameter of 10 mm, and the ball-to-material ratio is 3:
1.
5. The method for preparing a ceramic material according to claim 2, characterized in that: The green density of the molding is controlled at 1.75±0.05g / cm after isostatic pressing. 3 .
6. The method for preparing a ceramic material according to claim 2, characterized in that: The amount of the boron trioxide used is 5 times the mass of the boron carbide skeleton.
7. The method for preparing a ceramic material according to claim 2, characterized in that: The three-stage heating is as follows: the first stage: temperature 350°C, insulation for 2 hours, ammonia flow rate of 15 ml / min; the second stage: temperature 800°C, insulation for 1 hour, ammonia flow rate of 35 ml / min; the third stage: temperature 1200°C, insulation for 3 hours, ammonia flow rate of 5 ml / min.
8. The method for preparing a ceramic material according to claim 2, characterized in that: The three-stage heating has a heating rate of about 5°C / min between each stage.
9. The method for preparing a ceramic material according to claim 2, characterized in that: When the ratio of 20 μm boron carbide micropowder to 1 μm boron carbide micropowder is greater than 9:1, a secondary nitriding treatment is added after the polishing treatment.
10. The method for preparing a ceramic material according to claim 9, characterized in that: The secondary nitriding treatment is specifically as follows: boron trioxide powder is sprinkled on the working surface of the boron carbide skeleton, and then it is placed in a vacuum furnace, evacuated, and heated to 850°C, and kept warm for 2 hours. After the boron trioxide is melted, a layer of boron trioxide glaze layer will be formed on the working surface of the boron carbide skeleton, and then it is placed in a nitriding furnace for nitriding treatment.